2006
DOI: 10.1111/j.1749-7345.2006.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Production Characteristics, Water Quality, and Costs of Producing Channel Catfish Ictalurus punctatus at Different Stocking Densities in Single‐batch Production

Abstract: Channel catfish Ictalurus punctatus farming is the largest component of aquaculture in the USA. Culture technologies have evolved over time, and little recent work has been conducted on the effects of stocking density on production characteristics and water quality. Twelve 0.1‐ha ponds were stocked with 13‐ to 15‐cm fingerlings (16 g) at either 8600, 17,300, 26,000, or 34,600 fish/ha in single‐batch culture with three replicates per treatment. Fish were fed daily to apparent satiation with a 32% floating comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 15 publications
(29 reference statements)
4
52
4
Order By: Relevance
“…However, the understocked fingerlings were significantly smaller at the end of the year when fed every other day. Growth and yield of these smaller fish that were carried over into year 2 production were projected from data reported by Southworth et al (2006b). The result was that marketable yield in year 2 was only 3,575 kg/ha (2,861 kg/ha less than annual yields when fish were fed every day), which was below the 4,955 kg/ha estimated as the break-even yield for average farm sizes (Engle 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the understocked fingerlings were significantly smaller at the end of the year when fed every other day. Growth and yield of these smaller fish that were carried over into year 2 production were projected from data reported by Southworth et al (2006b). The result was that marketable yield in year 2 was only 3,575 kg/ha (2,861 kg/ha less than annual yields when fish were fed every day), which was below the 4,955 kg/ha estimated as the break-even yield for average farm sizes (Engle 2007).…”
Section: Resultsmentioning
confidence: 99%
“…With the 44% average fingerling survival of year 1, there would be 7,040 carryover fish/ha for a biomass of 1,190 kg/ha. Growth rates for year 2 were taken from Southworth et al (2006b) for similar stocking rates. Mean FCRs from the present study were used to calculate feed quantities for 1 ha of production by multiplying the yield by the FCR for each feeding regime to estimate the cost of the feed per hectare.…”
Section: Methodsmentioning
confidence: 99%
“…Previous pond studies at the University of Arkansas at Pine Bluff (UAPB) have looked at a variety of single and multiple-batch characteristics of both fingerlings (6.7 cm-17.8 cm; Engle & Valderrama, 2001;Pomerleau & Engle, 2003;Pomerleau & Engle, 2005a, Pomerleau & Engle, 2005bSouthworth, Stone, & Engle, 2006a;Southworth, Stone, & Engle, 2006b) and stocker size catfish (55 g-361 g; Pomerleau & Engle, 2003;Green & Engle, 2004;Pomerleau & Engle, 2005a, b). A small stocker is a fish in the size range of 27 g-82 g and a large stocker is a fish in the size range of 82 g-340 g (USDA, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Feed was estimated for all densities with an assumed FCR of 1.75 based on a 2004 multiple-batch study done at UAPB (Southworth, Stone, & Engle, 2006b). Many single-batch studies (Busch, 1984;Pomerleau & Engle, 2003;Green & Engle, 2004;Southworth, Stone, & Engle, 2006a) and multiple-batch studies (Engle & Valderrama, 2001;Tucker et al, 1993;Southworth, Stone, & Engle, 2006b) conducted in the past have found no significant differences in FCR due to varying stocking densities, with conversion values ranging from 1.0 to 2.0. In the current study, sensitivity analyses were done by varying FCR from 1.0 to 2.0.…”
mentioning
confidence: 99%
“…Data for growth, survival, and yield in multiple-batch production of fingerlings and carryover fish were taken from Engle and Valderrama (2001), Engle et al (2009) and Nanninga and Engle (2010) for various feeding strategies (Tables 2 and 3). Performance of the three different stocker weight classes when fed with different feeding strategies was adopted from the performance of similar weight classes of stockers from Green and Engle (2004), Pomerleau and Engle (2005) and Southworth et al (2006) ( Table 4). The initial model used a feed price of $440=MT and a catfish price of $2.76=kg, with unlimited access to operating capital and labor.…”
Section: Optimizing Catfish Feeding and Stocking Strategies 173mentioning
confidence: 99%